The international location decision: a study of manufacturing firms. (16th March 2022) - Touray, Ebou; Schmidt, Andreas; Hansen, Zaza
The aim of this paper is to build a broader understanding of the international location decision (ILD) of manufacturing by investigating and mapping Danish manufacturing firms' related activities and underlying processes. Using an exploratory survey approach on 17 Danish firms, the study shows there is less emphasis on cost than in past studies and a large unstructured human influence. A framework containing six categories of ILD factors - cost, labour and social characteristics, infrastructure, politics and regulations, economics and markets and resources - and an assessment of their respective single factors are presented. Lastly, the paper identifies five major shortcomings in the current practice: unstructured processes, non-involvement of the operational level of the organisation, static perspective of dynamic factors, uneven balance between quantitative and qualitative factors and no organisational learning. For engineering managers facing an ILD, the insights in this paper can be used to reflect and identify potential shortcomings in own practice of ILDs and help refocusing future process designs.